REFORMASI BIROKRASI ALA PEMERINTAH KOTA PONTIANAK (BUREAUCRATIC REFORM BY THE GOVERNMENT OF PONTIANAK CITY) - Lany Erinda Ramdhani, dan Tri Noor Aziza, Rustan A., Fani Heru Wismono (Jurnal Borneo Administrator, 2014)
This study aims to identify the characteristic of bureaucratic reforms implemented by the government of Pontianak City. Some innovation has been successfully carried out in order to speed up public services, thus have an impact on increase of public confidence. The results of this study indicate that the role of strong leadership from the Mayor of Pontianak City(Sutarmidji) and public interaction factor becomes an important element in the implementation of bureaucratic reform in Pontianak. Furthermore, in the context of change management, in order to accelerate the bureaucratic reform in Pontianak, local government using power-coercive approach and normative-re-educative approach. Both of these approaches have succeeded in altering the face of Pontianak City bureaucracy becomes: serve the public better, providing excellent service, fast, cheap and even free, safe, easy, transparent,and fair.Keywords : bureaucratic reform, the government of Pontianak CityStudi ini bertujuan untuk menemukenali ciri khas reformasi birokrasi yang diterapkan oleh Pemerintah Kota Pontianak. Beberapa pembaharuan/inovasi telah berhasil dilakukan dalam rangka mempercepat pelayanan publik dan meningkatkan kepercayaan publik. Hasil kajian ini menunjukkan bahwa peran kepemimpinan yang kuat dari Walikota Sutarmidji dan faktor interaksi publik dengan penyelenggara pemerintahan menjadi elemen penting dalam pelaksanaan reform di tubuh birokrasi Kota Pontianak. Adapun pendekatan manajemen perubahan yang diterapkan dalam rangka percepatan reformasi birokrasi di lokus penelitian ini adalah pendekatan kekuasaan-koersif dan pendekatan normatif-reedukatif. Kedua pendekatan ini telah berhasil mengubah wajah birokrasi Kota Pontianak menjadi lebih melayani publik,prima, cepat, murah dan bahkan gratis, aman, mudah, transparan, dan adil.Kata Kunci : Reformasi Birokrasi, Pemerintah Kota Pontianak